KONSEP MODEL PEMBELAJARAN ANI-LBL DALAM MERESPON PROBLEMATIKA PAI DI PERGURUAN TINGGI - Hamidah, Ani Mar'atul; Ahid, Nur (LP2M IAI Muhammadiyah Bima, 2025)
The core issue in Islamic Religious Education at the university level lies in the gap between learning content and the contextual needs of students from diverse educational backgrounds. This misalignment weakens the internalization of Islamic values in real life. This article introduces the ANI-LBL learning model as an innovative conceptual response. ANI stands for Analytical Content, Normative Knowledge, and Interdisciplinary Approach, emphasizing the integration of critical thinking, normative values, and interdisciplinary approach. Combined with Life Based Learning (LBL), this model connects learning to students’ real-life experiences. The study employs a descriptive qualitative approach, using observation and literature review as data collection techniques. The integration of the ANI-LBL model gives the learning syntax results: orientation, analytical content, normative knowledge, interdisciplinary approach, information processing, information delivery and discussion, evaluation and feedback. This concept is expected to serve as an initial framework for developing contextual and holistic PAI learning designs in higher education institutions.